(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the epidemiological characteristics, computed tomography, and surgical results of traumatic penetrating brain injuries. Subjects and methods: A cross-sectional descriptive study on 51 patients, diagnosed with penetrating brain injuries, operated on at Thai Nguyen National Hospital from January 2020 to May 2025. Results: In 51 cases of penetrating brain injuries, the average age was 29.65 years old; 94.1% were male and 5.9% were female. The cause of injury was due to traffic accidents 62.7%. CT scan shows that intracranial aerocele appeared in 94,1% of patients; 54.9% of patients did not record midline shift on CT scan, 27.5% had midline shift of ≤ 5 mm, average hospital stay was 19.8 days. 82.4% of patients were conscious upon discharge from hospital. Surgical results after 3 months evaluated according to GOS scale: good 62.7%; death 9.8%. Conclusion: Traffic accidents account for a high proportion of the causes. Surgery to treat penetrating brain injuries at Thai Nguyen National Hospital has good results. However, patients with severe conditions upon admission have poor treatment outcomes and low recovery after surgery.